2023
DOI: 10.1063/5.0136469
|View full text |Cite
|
Sign up to set email alerts
|

Dual frequency ultrasonic cavitation in various liquids: High-speed imaging and acoustic pressure measurements

Abstract: Ultrasonic cavitation is used in various processes and applications, utilising powerful shock waves and high-speed liquid jets generated by the collapsing bubbles. Typically, a single frequency source is used to produce the desired effects. However, optimisation of the efficiency of ultrasound reactors is necessary to improve cavitation activity in specific applications such as for the exfoliation of two dimensional (2D) materials. This research takes the next step to investigate the effect of a dual frequency… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
9
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 12 publications
(16 citation statements)
references
References 45 publications
0
9
0
Order By: Relevance
“…This showcases ultrasonication's efficiency over reflux, attributed to its cavitation effect induced by ultrasonic or acoustic waves causing bubble formation and bursting in liquids. The presence of ultrasonic waves will increase the number of active cavitation bubbles which will increase the efficiency of the reaction by increasing the reaction rate, speeding up the reaction, 18 and increasing the local temperature and pressure of the liquid 20,21 . Therefore, the Cannizzaro reaction using the ultrasonic method is faster than the reflux method.…”
Section: Results and Discussion Cannizzaro Reaction Using Ultrasonica...mentioning
confidence: 99%
See 1 more Smart Citation
“…This showcases ultrasonication's efficiency over reflux, attributed to its cavitation effect induced by ultrasonic or acoustic waves causing bubble formation and bursting in liquids. The presence of ultrasonic waves will increase the number of active cavitation bubbles which will increase the efficiency of the reaction by increasing the reaction rate, speeding up the reaction, 18 and increasing the local temperature and pressure of the liquid 20,21 . Therefore, the Cannizzaro reaction using the ultrasonic method is faster than the reflux method.…”
Section: Results and Discussion Cannizzaro Reaction Using Ultrasonica...mentioning
confidence: 99%
“…Table 1. is the result of the energy calculation of the ultrasonication and reflux method which is obtained from the formula of the equation that has been reported by 30 on research by 21 . According to Table 1.…”
Section: Energy Comparisonmentioning
confidence: 99%
“…[22,23] However, cavitation events need a high acoustic pressure and continuously stable cavitation nuclei, [24,25] which is also difficult to control because any pocket present in the tissue may act as a nucleation site for initiation of random cavitation events. [26,27] Previous work involving the microbubbles contrast agents, [28,29] phase-shift perfluorooctyl bromide nanovesicles, [30] and perfluorohexane-encapsulated fullerene [31] into ultrasonic histotripsy has been proven to be an efficient method to increase cavitation nuclei and reduce cavitation threshold. [32][33][34][35] However, this method is still unsatisfactory since they allow cavitation for a very short time under pHIFU due to the rupture of their stabilizing gas shells.…”
Section: Doi: 101002/smll202302744mentioning
confidence: 99%
“…[ 22,23 ] However, cavitation events need a high acoustic pressure and continuously stable cavitation nuclei, [ 24,25 ] which is also difficult to control because any pocket present in the tissue may act as a nucleation site for initiation of random cavitation events. [ 26,27 ]…”
Section: Introductionmentioning
confidence: 99%
“…Due to the secondary acoustic radiation generated by cavitation bubbles in ultrasound fields, bubble-bubble interactions should be considered to explain cavitation effects, such as the promotion or suppression of bubble oscillations, [1] which also depend on the splitting, polymerization, and nonspherical deformation of bubbles. [3][4][5][6] When multiple bubbles coexist in cavitation field, the coupling effect of bubbles cannot be ignored. Haghi et al [7] studied the collective nonlinear behaviors of bubbles in polydisperse bubble clusters, and found that the large microbubbles in clusters can force the small microbubbles to generate periodic frequency doubling and subharmonic oscillation.…”
Section: Introductionmentioning
confidence: 99%